Kedudukan dan Peran Kepemimpinan Lembaga Wali Nanggroe dalam Pemerintahan dan Adat Aceh menurut Pandangan Imam Al-Mawardi - Desi Desma Syahri; Badri; T. Surya Reza (Lembaga Yasin AlSys, 2026)
The Wali Nanggroe Aceh Institution, as a customary leadership institution, holds a strategic position and performs strategic functions in the life of Acehnese society, but it has not been widely examined from the perspective of Islamic constitutional law, particularly Imam Al-Mawardi’s theory of imamah. This study aimed to analyze the position and role of the Wali Nanggroe Institution in Acehnese governance and customary affairs based on the views of Imam Al-Mawardi. This study employed a normative juridical method by examining theories, ideas, and legal provisions related to the position and role of the Wali Nanggroe Institution. The results showed that the Wali Nanggroe Institution holds the position of an independent and authoritative customary leadership institution operating outside the formal governmental structure. This institution plays a role in upholding dīn al-Islām, unifying Acehnese society, conducting guidance, taqnīn, and supervision, and promoting the realization of justice and prosperity. From Imam Al-Mawardi’s perspective, this position and these roles are relevant to the concept of imamah, particularly in performing the function of ḥirāsat al-dīn, or safeguarding religion, preserving the welfare of the community, strengthening social unity, and providing counsel and guidance to leaders and society. Nevertheless, a fundamental difference exists because the Wali Nanggroe does not possess the political and governmental authority held by an imam in Al-Mawardi’s theory but instead functions as a moral, social, and cultural leader. This study confirms that Islamic leadership values can be adapted within modern customary institutions without necessarily being embodied in formal political authority. These findings contribute to the development of scholarship on Islamic constitutional law, customary law, and regional governance in the context of Aceh’s special autonomy.